IMPACT OF FOREIGN CAPITAL FLOWS ON ECONOMIC GROWTH IN NIGERIA: 1986-2023 - Oniore , Jonathan Ojarikre; Ogwuche , David Dauda; Audu , Ephraim A (International Journal of Allied Research in Economics (IJARE), 2024)
Recipient nations, including developed and developing economies, stand to benefit greatly from foreign capital inflows. They transfer managerial and technological know-how that can promote long-term economic growth, and financial resources for investments. However, international capital flows can intensify macroeconomic imbalances and increase the economy’s growth susceptibility. As a result, this research uses time series data from 1986 to 2023 to examine how foreign capital flows affect economic growth. Fully modified ordinary least squares (FMOLS) Regression was employed as the main analytical technique. The findings show that, over the long term, two of the four explanatory variables considered in this investigation have a statistically significant impact on Nigeria’s economic growth. By implication, FDI inflows and personal remittances explain Nigeria’s economic growth throughout the research period. FDI inflows are significant but inversely connected with economic growth, according to the paper’s variable-by-variable analysis. Additionally, the long-term estimated impact of official development assistants on economic growth is insignificant but positive. Conversely, the results show that over time, personal remittances seem to have a major and favorable impact on economic growth. However, the findings show that foreign debt stocks have a negative and insignificant impact on economic growth. Consequently, the paper suggested that rather than extractive industries, which might not have as much positive spillover to the overall economy, the Federal government and other tiers of government should target growth-enhancing FDI by focusing on sectors that have higher value-added potential, like technology, manufacturing, and infrastructure. Additionally, the federal government should enact measures—like lowering transaction fees that facilitate and lower the cost of money transfers through official channels for Nigerians living outside.